Potential of Lactoferrin in the Treatment of Lung Diseases - Katarzyna Kaczyńska; Monika Jampolska; Piotr Wojciechowski; Dorota Sulejczak; Kryspin Andrzejewski; Dominika Zając (MDPI AG, 2023)
Lactoferrin (LF) is a multifunctional iron-binding glycoprotein that exhibits a variety of properties, such as immunomodulatory, anti-inflammatory, antimicrobial, and anticancer, that can be used to treat numerous diseases. Lung diseases continue to be the leading cause of death and disability worldwide. Many of the therapies currently used to treat these diseases have limited efficacy or are associated with side effects. Therefore, there is a constant pursuit for new drugs and therapies, and LF is frequently considered a therapeutic agent and/or adjunct to drug-based therapies for the treatment of lung diseases. This article focuses on a review of the existing and most up-to-date literature on the contribution of the beneficial effects of LF on the treatment of lung diseases, including asthma, viral infections, cystic fibrosis, or lung cancer, among others. Although in vitro and in vivo studies indicate significant potency of LF in the treatment of the listed diseases, only in the case of respiratory tract infections do human studies seem to confirm them by demonstrating the effectiveness of LF in reducing episodes of illness and shortening the recovery period. For lung cancer, COVID-19 and sepsis, the reports are conflicting, and for other diseases, there is a paucity of human studies conclusively confirming the beneficial effects of LF.